We will have the following:
First, we determine the derivative of the expression, that is:
![y=9ln((e^x+e^(-x))/(2))\Rightarrow y^(\prime)=(9(e^(2x)-1))/(1+e^(2x))](https://img.qammunity.org/2023/formulas/mathematics/college/k2gcxk3qqxxrvy1r0vx7f3r31sr6ebobhn.png)
Now, we determine the value of the slope at x = 0, that is:
![y^(\prime)(0)=(9(e^(2(0))-1))/(1+e^(2(0)))\Rightarrow y^(\prime)(0)=(9(1-1))/(1+1)\Rightarrow y^(\prime)(0)=0](https://img.qammunity.org/2023/formulas/mathematics/college/klor2a0itfrrwv40enk15g1rndkhx7ym7x.png)
So, from this we will have that the equation of the line that is tangent for the function at the point (0, 0) will be:
![y-0=0(x-0)\Rightarrow y=0](https://img.qammunity.org/2023/formulas/mathematics/college/9jddlhjyywqvjzlovyhlu6u6hxa5rfgn98.png)
So, the equation of the line will be:
![y=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/5vm2i52uqdka0dixzzefmp92421iv5xkk7.png)
This can be seeing as follows: